The relative contributions of diet and associated microbiota to the accumulation of UV-absorbing mycosporine-like amino acids in the freshwater copepod Boeckella antiqua - Perez, Alejandra Patricia (2012)
1. Mycosporine-like amino acids (MAAs) are ubiquitous compounds in aquatic organisms that are usually considered sunscreens that protect them from harmful ultraviolet radiation. Given that virtually all animals lack the metabolic pathways to synthesise MAAs de novo, they must acquire them either from their diet or from microorganisms living in close association. In freshwater copepods, accumulation of MAAs is stimulated by exposure to ultraviolet and/or visible radiation. 2. A 2×2 factorial experiment was performed to assess the contributions of dietary and microbial sources of MAAs in the freshwater copepod Boeckella antiqua. The treatments consisted of two different diets: an MAA-free diet, including only Chlamydomonas reinhardtii, and an MAA-rich diet, including both C. reinhardtii and Peridinium inconspicuum, crossed with two antibiotic treatments, with and without chloramphenicol. Treatment with chloramphenicol was intended to inhibit the development of bacteria associated with the copepods. 3. MAA concentration in B. antiqua was affected by the experimental conditions: (i) exposure to artificial PAR+UVR stimulated the accumulation of several MAAs (up to 62% increase in total MAA concentration with respect to the initial concentration); (ii) the presence of chloramphenicol in the culture media reduced the MAA concentration in copepods fed an MAA-free diet; (iii) in the absence of chloramphenicol, copepods fed the MAA-rich diet had significantly higher total MAA concentration than those fed the MAA-deficient diet; but (iv) dietary supplementation with an MAA-rich algae in the presence of chloramphenicol failed to significantly increase total MAA concentration. 4. Analysis of profiles from denaturing gradient gel electrophoresis (DGGE) showed that the prokaryotic community associated with the copepods was affected by chloramphenicol. Dendograms constructed from digitalised DGGE images consistently grouped the antibiotics treatments separately from the initial samples and the treatments without antibiotics. Two band positions were exclusive to treatments without antibiotics. 5. We conclude that when offered an MAA-rich diet, B. antiqua may accumulate a proportion of MAAs from diet. However, we suspect that in the absence of an MAA-rich dietary source (as in its natural habitat), virtually all MAAs present in B. antiqua are produced by copepod-associated prokaryotes.